Effect of Important Food Sources of Fructose-Containing Sugars on Biomarkers of Inflammation: A Systematic Review and Meta-Analysis of Controlled Trials. (7th June 2021) - Qi, XinYe; Chiavaroli, Laura; Lee, Danielle; Ayoub-Charette, Sabrina; Khan, Tauseef; Au-Yeung, Fei; Ahmed, Amna; Cheung, Annette; Liu, Qi; Mejia, Sonia Blanco; de Souza, Russell; Wolever, Thomas; et al.
Abstract: Objectives: Excess calories as fructose may initiate pathways increasing biomarkers of inflammation. Whether this effect is mediated by the food matrix at different energy levels is unknown. We conducted a systematic review and meta-analysis of controlled feeding trials of the effect of food sources of fructose-containing sugars at different energy control levels on biomarkers of inflammation (NCT02716870). Methods: We searched MEDLINE, Embase, and the Cochrane Library through January 15 2020 for controlled trials ≥7d. Trial designs were prespecified based on energy control: substitution (energy-matched replacement of sugar in the diet); addition (excess energy from sugar added to diets); subtraction (energy from sugar subtracted from diets); ad libitum (energy from sugar freely replaced in the diet). The primary outcome was C-reactive protein (CRP). Secondary outcomes were tumor necrosis factor-alpha (TNF-α) and interleukin 6 (IL-6). Independent reviewers extracted data and assessed the risk of bias. Certainty of evidence was assessed by GRADE. Results: We included 48 trials (109 trial comparisons, n = 2108) assessing the effect of 10 food sources (SSBs, sweetened dairy, sweetened dairy alternatives (soy), fruit, 100% fruit juice, dried fruit, sweetened cereal grains/bars, sweets, added nutritive sweetener, and mixed sources) across the 4 levels of energy control. Total fructose-containing sugars had no effect on any outcome in any level of energy control. There was evidence of interaction by food source; in substitution trials, sweetened dairy alternative (soy) decreased CRP. In addition trials, fruit decreased while added nutritive sweetener increased TNF-α. The certainty of evidence was low for the effect of sweetened dairy alternative (soy) on CRP in substitution trials, and generally moderate for all other comparisons. Conclusions: Food source more than energy control appears to mediate the effect of fructose-containing sugars on inflammation. The evidence provides some indication that sweetened dairy alternatives (soy) and fruit decrease and added nutritive sweeteners increase biomarkers of inflammation. More high-quality randomized trials of different fructose containing food sources are needed to improve our estimates. Funding Sources: Diabetes Canada.